THE EFFECT OF RECIPROCAL TEACHING STRATEGY TOWARDS THE STUDENTS’ READING COMPREHENSION - AINAA, RAISA AINAA (Faculty of Tarbiyah nad Teacher Training, 2022)
This research is based on a quantitative analysis with experimental design. The objective of this study is to find out whether Reciprocal Teaching Strategy has significant effect towards the students' reading comprehension at the third grade of senior high school. The subject of this research is the students at SMA NEGERI 1 Lhokseumawe. Therefore, the researcher divided the class into two classes, there are experimental and control class. The experimental class was applying Reciprocal Teaching Strategy on the learning process meanwhile the control class was applying conventional strategy.. From the pre- test has been found that the Students’ mean score is 59 and then the score increased to 82. However, for the control class the Students’ mean score on pre-test were 66.5 and the post- test was not increasing significantly as the mean score is 80. Furthermore, based on the data tobservedvalue is 2.40 which higher than ttable at the significant level 0.05 (2.40> 1.67). It can be concluded that Reciprocal Teaching Strategy has significant effect towards the students’ reading comprehension because the result showed that the alternative hypothesis (Ha) is accepted and H0 is rejected.